Prolonged In Vivo Chemogenetic Generation of Hydrogen Peroxide by Endothelial Cells Induces Cardiac Remodelling and Vascular Dysfunction - Melina Lopez; Niklas Herrle; Bardia Amirmiran; Pedro F. Malacarne; Julia Werkhäuser; Souradeep Chatterjee; Carine Kader; Victoria Jurisch; Xin Wen; Maedeh Gheisari; Katrin Schäfer; Christian Münch; et al. (Antioxidants)
Increased levels of reactive oxygen species (ROS) are a hallmark of cardiovascular disease. ROS impact the function of proteins largely through thiol modification leading to redox signalling. Acute, targeted interference with local ROS levels has been difficult. Therefore, how dynamics in redox signalling impact cardiovascular health is still a matter of current research. An inducible, endothelial cell-specific knock-in mouse model expressing a yeast D-amino acid oxidase enzyme was generated (Hipp11-Flox-Stop-Flox-yDAO-Cdh5-CreERT2+/0 referred to as ecDAO). DAO releases H2O2 as a by-product of the conversion of D-amino acids into imino acids. The D-amino acid treatment of DAO-expressing cells therefore increases their intracellular H2O2 production. The induction of yDAO in the ecDAO mice was performed with tamoxifen. Subsequently, the mice received D-Alanine (D-Ala, 0.5 M) through drinking water, and the effects on ROS production and vascular and cardiac function were determined. ecDAO induction increased endothelial ROS production as well as ROS production in the lung, which is rich in endothelial cells. The functional consequences of this were, however limited: After minimally invasive myocardial infarction, there was no difference in the outcome between the control (CTL) and ecDAO mice. With respect to vascular function, three days of D-Ala slightly improved vascular function as demonstrated by an increase in the diameter of the carotid artery in vivo and decreased vessel constriction to phenylephrine. Fifty-two days of D-Ala induced cardiac remodelling, increased peripheral resistance, and overoxidation of peroxiredoxins. In conclusion, acute stimulation of endothelial ROS improves cardiovascular function, whereas prolonged ROS exposure deteriorates it.